2007
DOI: 10.1021/ma062304x
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Series of Preceramic B-Tri(methylamino)borazine-Based Polymers as Fiber Precursors:  Shear Rheology Investigations

Abstract: Oscillatory shear flow of poly[B-(methylamino)borazine] was studied for suitability as a melt-spinnable material. Shear rheology experiments show that viscosity of molten poly[B-(methylamino)borazine] is temperature dependent following an Arrhenius-type equation. The high value of the flow activation energy is caused by the presence of branched chains and cross-linked portions in the polymer network which supply an intrinsic rigidity to the molecular architecture. Dynamic rheological properties of polymers wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 21 publications
(51 reference statements)
0
26
0
Order By: Relevance
“…It is reasonable to suggest that γ 0 = 10% represents an appropriate value to maintain constant dynamic moduli with deformation amplitude. [28] The good thermal stability of the precursor polymer in the melt was confirmed by such experiments, since values of G , G , and η * remain unchanged for short times. So this preceramic polymer exhibited non-Newtonian behavior during extrusion in the first stage.…”
Section: Rheological Properties Of Precursor Meltmentioning
confidence: 70%
See 1 more Smart Citation
“…It is reasonable to suggest that γ 0 = 10% represents an appropriate value to maintain constant dynamic moduli with deformation amplitude. [28] The good thermal stability of the precursor polymer in the melt was confirmed by such experiments, since values of G , G , and η * remain unchanged for short times. So this preceramic polymer exhibited non-Newtonian behavior during extrusion in the first stage.…”
Section: Rheological Properties Of Precursor Meltmentioning
confidence: 70%
“…[28] The determination of the linear viscoelastic region is an important step in dynamic rheological characterization testing. In this controlled-strain test, samples are heated and then deformed in oscillatory shear flow up to a maximum strain γ 0 , which must be small enough to be in the linear regime.…”
Section: Rheological Properties Of Precursor Meltmentioning
confidence: 99%
“…As an illustration, Fig. 5 shows the general thermo-mechanical behaviour of a polymer prepared at Table 1 Proportion of -N(CH 3 )-and -N(H)CH 3 units as a function of T thermolysis measured by 13 It is clearly observed that polymer swelling is reduced when the load used during TMA experiments is increased from 0.01 to 0.5 N.…”
Section: Thermo-mechanical Behaviourmentioning
confidence: 99%
“…Such results can be linked to rheological experiments which have been achieved for the same polymeric systems. 13 …”
Section: Thermo-mechanical Behaviourmentioning
confidence: 99%
See 1 more Smart Citation